2016
DOI: 10.1039/c6cp03723b
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on dihydropyrazine annulated linear polyacenes: aromaticity, stability and HOMO–LUMO energy modulation

Abstract: Linear polyacenes (LPAs) beyond pentacene are highly unstable and their application potential in the optoelectronics field is very limited. On the basis of theoretical studies at the M06L/6-311++G(d,p) level of DFT, we show that annulating dihydropyrazine units to LPA cores can yield large LPA mimics. This strategy enhances the aromaticity of the LPA core and also provides a way to modulate the HOMO-LUMO energy gap by choosing an appropriate LPA core and extending dihydropyrazine annulation. The study is condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 89 publications
0
17
1
2
Order By: Relevance
“…These values are significantly less negative than the V min value 26.1 kcal/mol observed for the BAH bond of BH 3 which support the extended delocalization of nitrogen lone pair in LPA mimics. Unlike the previously reported dihydropyrazine annulated molecules, [15] V min of azaborinine annulated systems show only minor variation in the values, particularly for the interior LPA units.…”
Section: Mesp and Electron Delocalizationcontrasting
confidence: 94%
See 2 more Smart Citations
“…These values are significantly less negative than the V min value 26.1 kcal/mol observed for the BAH bond of BH 3 which support the extended delocalization of nitrogen lone pair in LPA mimics. Unlike the previously reported dihydropyrazine annulated molecules, [15] V min of azaborinine annulated systems show only minor variation in the values, particularly for the interior LPA units.…”
Section: Mesp and Electron Delocalizationcontrasting
confidence: 94%
“…This indicates that BH and NH heterocenter connection is more stabilizing for a larger LPA unit. In the case of dihydropyrazine annulated LPA mimics described in a previous paper, average E dh for a ring is found to be 38.8 kcal/mol whereas in the present azaborinine incorporated systems, the average E dh 81.2 kcal/mol is very high meaning that the 1,4‐dihydro‐1,4‐azaborinine‐based LPA mimics are more stable than the dihydropyrazine‐based systems. The total increase in the dehydrogenation energy (∑ E dh ) is directly related with the increase in the number and size of the LPA units.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Recent experimental studies [50][51][52] have suggested the introduction of nitrogen atoms into the acene framework (aza-acenes) as one possible route to stabilize longer oligomers. Concomitantly, it has been shown theoretically 53,54 that the hydrogenated forms of aza-acenes with inner N substitutions possess one more aromatic sextet ring compared to their pristine acene counterparts, which explain qualitatively the higher stability of these N-rich compounds according to Clar's rule. 55,56 According to the above discussion based on natural orbital occupations and unpaired electron distributions, our results clearly demonstrate the possibility of tuning the radical character of acenes by means of chemical doping.…”
Section: Polyradical Charactermentioning
confidence: 96%
“…In this work, we applied the M06L functional with 6-31G** for C, H, O, N, and Br, and LANL2DZ for Ti, Ni, and Zr. The selection of the M06L functional is based on previous benchmark studies [46][47][48]. Zhao and Truhlar [46] reported that M06L has reasonably good overall performance, and it is the best functional for transition metal energetics, and for the study of organometallic and inorganometallic thermochemistry.…”
Section: Electronic Propertiesmentioning
confidence: 99%